Challenges Encountered by Head Teachers in the Administration of Pupils' Indiscipline in Primary Schools in Anambra State - Umeji, Ifeoma Chinyere (PT. Pusmedia Group Indonesia, 2024)
This study investigates the difficulties experienced by head teachers in dealing with pupils' indiscipline in primary schools in Anambra State, Nigeria. Utilizing an unmistakable examination plan, information was gathered from head teachers through organized polls and semi-organized interviews. The study uncovered a few difficulties, remembering troubles for recognizing main drivers of indiscipline, guaranteeing consistency in disciplinary activities, tending to peer strain and social elements, and overseeing huge class sizes. Regardless of these difficulties, head teachers executed different systems to oversee indiscipline, including cultivating positive connections, empowering open correspondence channels, offering advising and support benefits, and advancing pupil contribution in dynamic cycles. The findings highlight the significance of proactive intercessions and cooperative endeavors among school partners to actually address indiscipline. This study adds to the current writing by giving bits of knowledge into the one of a kind difficulties encountered by head teachers in Anambra State and gives proposals for working on disciplinary practices in primary schools